Combined extracorporeal membrane oxygenation and microaxial pump—when left ventricular preload is too low to unload in cardiogenic shock. Issue 3 (9th July 2021) - Lüsebrink, Enzo; Massberg, Steffen; Orban, Martin
Abstract: Purpose: Severe cardiogenic shock is the major driver of mortality on cardiologic intensive care units. Novel therapeutic options like extracorporeal membrane oxygenation (ECMO) or the combination of ECMO and a percutaneous microaxial pump like Impella CP (ECMELLA) are promising Options. Here we want to focus on the question what happens when left ventricular preload is too low to unload in cardiogenic shock in patients with ECMELLA and this aspect is illustrated by transesophageal echocardiography. Methods: We detail a case of a 43‐year‐old active smoker who was admitted for acute myocardial infarction causing severe cardiogenic shock and who was finally treated with ECMELLA. Transesophageal echocardiography is used to illustrate what happens when left ventricle (LV) preload is too low to unload. Results: Transesophageal echocardiography demonstrates complete collapse of LV and LA as consequence of increased but still low flow rate of the coaxial pump. Conclusion: Novel therapeutic options like ECMO and percutaneous microaxial pumps like Impella CP, 5.0 or the combination of both (ECMELLA), are promising options. Whether these approaches reduce mortality has to be evaluated in urgently needed randomized trials but results will not be available in the next few years.